PsycEXTRA Dataset 2010
DOI: 10.1037/e741462011-004
|View full text |Cite
|
Sign up to set email alerts
|

Racial identity, father involvement, and coparenting in adolescent African American mothers and fathers

Abstract: Adolescent childbearing is a major public policy concern in the United States, and father involvement is a particular focus for researchers and members of socioeconomically disadvantaged and minority populations. In the present study, 52 lowincome, African American adolescent mothers and their children's fathers were interviewed during the prenatal period about their relationships, social networks, and racial identity. Coparenting was found to be associated with racial identity in that mothers and fathers who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Coparenting refers to the extent to which both parents are invested in a child, value the other parent’s input and involvement with the child, respect each other’s judgment, and have a desire to talk to each other about their child (Varga & Gee, 2010; Weissman & Cohen, 1985). Similar to parenting stress, economic hardship may put strain on the ability for parents to work together as effective coparents, which also may put strain on the stability of the relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coparenting refers to the extent to which both parents are invested in a child, value the other parent’s input and involvement with the child, respect each other’s judgment, and have a desire to talk to each other about their child (Varga & Gee, 2010; Weissman & Cohen, 1985). Similar to parenting stress, economic hardship may put strain on the ability for parents to work together as effective coparents, which also may put strain on the stability of the relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A common theme in the literature regarding NCAAFs is that they had fewer intact and consistent relationships with their children than noncustodial fathers of other races. In addition to grappling with the hindrances mentioned above, other distinct issues NCAAFs reported as impediments to their involvement and engagement include being more likely to have nonexistent or infrequent contact with their fathers during childhood (Varga, 2011), a history of incarceration (Arditti et al, 2019), and increased psychological distress (Yuan, 2016). However, in a more positive light, NCAAFs who were involved in their children's lives have been found to have higher quality father-child interactions and relationships than those of other races (Ellerbe et al, 2018;Yuan, 2016).…”
Section: Literature On Ncaaf Parental Involvementmentioning
confidence: 99%
“…On the contrary, however, other race-based comparative studies have presented different results. For example, Varga (2011) found that NCAAFs fathers were less likely to be involved during the prenatal phase of child development than their Caucasian and Hispanic/Latino counterparts. Gee et al, 2007 posited that NCAAFs offered less in-kind paternal involvement and support than Caucasian and Latino fathers.…”
Section: Literature On Ncaaf Parental Involvementmentioning
confidence: 99%